Engineering component-based net-centric systems for embedded applications. - Jahnke, Jens H. (Software engineering notes.)
The omnipresence of the Internet and the World Wide Web (Web) via phone lines, cable-TV, power lines, and wireless RF devices has created an inexpensive media for telemonitoring and remotely controlling distributed electronic appliances. The great variety of potential benefits of aggregating and connecting embedded systems over the Internet is matched by the currently unsolved problem of how to design, test, maintain, and evolve such heterogeneous, collaborative systems. Recently, component-oriented software development has shown great potential for cutting production costs and improving the maintainability of systems. We discuss component-oriented engineering of embedded control software in the light of emerging requirements of distributed, net-centric systems. Our approach is baed on applying the graphical specification language SDL for composing complex networks of embedded software components. From the SDL specification, we generate internet-aware connector components to local embedded controller networks. The described research is carried out in a collaborative effort between industry and academia.